A review of practices and digital technology integration in reading instruction and suggestions for the Philippines - Esteban, Allan Jay; Calang, Ken; Pagador, Princes Mara E. (International Journal of Evaluation and Research in Education (IJERE), 2024)
Reading literacy has been a challenge in the Philippines based on recent large-scale literacy assessment in two consecutive years. This may be a result of a mismatch between reading instruction and the interest and motivation of students as 21st century learners in improving their reading skills. However, it is early to instigate such assumption. Hence, this systematic review examines eight articles related to reading instruction research in the Philippines and seven articles on digital technology integration for reading instruction. The paper finds no research on digital technology integration for reading instruction in the Philippine context, while studies conducted in other countries show the efficiency of digital technology interventions in reading literacy development. The findings emphasize the necessity for digital technology research in the reading instruction in the country. This report recommends empirical studies, curriculum adjustments, teacher training, and community engagements on technology-enabled reading education. Based on the findings of this study and a review of related literature, the PREACT framework (Policy, Research, Empirical study, Curriculum and resource adaptation, Community engagement and access, Teacher training and development) is proposed as a potential approach to transform reading instruction in the Philippines.